Evaluación física, sensorial y bromatológica del licor de cacao en variedades clonales EET-19, EET-48, EET-62, EET-96. EET-103 en la ESPAM - Mera Morán, Olaya Leonor (2014)
The purpose of this investigation was to evaluate the cacao liquor of six varieties of national clone cocoa in the ESPAM - MFL (Agricultural Polytechnic Superior School of Manabí - Manuel Félix López); physical, sensorial and bromatological variables were analyzed during winter (February-March) and summer (October-November ), For the evaluation the cocoa pod were harvested with the appropriate degree of maturity and carried out the process of post harvesting of the beans for the elaboration of cacao liquor of each clone in the INIAP (National Institute of Agricultural Investigations), physical parameters were evaluated in beans (capacity of fermentation, weight of seeds, head and cotyledon), sensorial (basic and specific flavors) and bromatological (acidity, pH, ash and content of fat). There were significant differences (p <0,05) in all the clones that are influenced by the stationary times. The adult obtained a fermentation of 96,50% in the clone EET-19 (Estación Experimental Tropical) during summer and 77,50% of the clone EET-103 during winter being low for the INEN 176 for all the physical variables, the content of fat in winter was below 50% while in summer was above that value, the specific flavors were bound to the appropriate to the fermentative process of the beans. It was conclude that the clone varieties evaluated presented characteristic sensorial differences, with medium and high level on basic flavors and very pleasant specific details and tend to vary physical and bromatological levels in stationary times.